Identification of genetic diversity among some promising lines of rice under drought stress using SSR markers. Issue 1 (1st January 2021) - Gaballah, Mahmoud M.; Fiaz, Sajid; Wang, Xiukang; Younas, Afifa; Khan, Sher Aslam; Wattoo, Fahad Masoud; Shafiq, Muhammad Rizwan
Abstract : Fourteen rice lines and one cultivar were investigated for morphological traits and genetic diversity under normal and drought stress condition. Mean squares of years, environment and lines × environments were significant for all traits under observation, except for days to heading and grain yield/plant in years, days to heading in environment and days to heading and harvest index in lines × environments, respectively. The 10 SSR markers, covering seven chromosomes (1, 2, 4, 5, 6, 8 and 9) generated polymorphic alleles with sum of 72 alleles on seven chromosomes with 9 markers across the fifteen rice lines. Furthermore, genetic diversity values for all SSR markers varied from 0.94 to 1.00 with an average of 0.98. In addition, the PIC values ranged from 0.83 to 0.99 with an average value of 0.94. The promising lines of present investigation can be utilized in future plant breeding programs.